Financial Analysis of PT. Unilever Indonesia Tbk Using The Economic Value Added (EVA) Method for The Period 2020–2025 - Novi Anggraini; Faizah Nabila; Putri Guslia; Agustina Wulandari; Nurul Depty Anggraini; Hasan Subaidi; Yossinomita Yossinomita (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk during the 2020–2025 period using the Economic Value Added (EVA) method. The EVA method measures a company's ability to create economic value after accounting for the total cost of capital employed. This study employs a quantitative descriptive approach using secondary data obtained from the company’s annual financial reports published on the Indonesia Stock Exchange. The analysis was conducted by calculating the main components of EVA, namely Net Operating Profit After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost of Capital (WACC), Capital Charges (CC), and Economic Value Added (EVA). The results of the study indicate that PT Unilever Indonesia Tbk successfully generated positive EVA values during the 2020–2025 period. All EVA values were above zero (EVA > 0), indicating that the company was able to create economic value added and meet the expectations of shareholders and creditors. However, EVA showed a declining trend throughout the observation period due to decreasing operating profit and changes in capital costs. This study concludes that PT Unilever Indonesia Tbk has demonstrated sound financial performance during the study period and has been able to manage its capital effectively in creating economic value. Keywords: Financial Performance, Unilever, EVA, WACC, NOPAT